Lake Taihu, China Dynamics and Environmental Change - Qin, Boqiang (Monographiae Biologicae,, 2008)
There are many shallow lakes in the world. Many of them play an important socio-economic role as contributors to the drinking water supply, in flood attenuation, fisheries and recreation activities. Because of the current anthropogenic changes in the environment, such lakes rapidly respond to eutrophication and swamping. It is often hard to address these issues because many changes in the ecosystems of shallow lakes are associated with little studied physical processes. This interaction between the aquatic biota and the physical and chemical environment increases the complexity of shallow lake ecosystems. Lake Taihu, located in the delta of Yangtze River, is a typical large, shallow eutrophic lake with area of 2338 km2 and maximum depth of less than 3m . This book provides basic data on various aspects of this lake and summarizes research work on the interaction between its ecology and physical limnology. It will be a reference for teachers and students of freshwater ecology and biology, the aquatic environment in general, and, most strikingly, for all those interested in physical limnology.